Clinico physiological Evaluation of Levobupivacaine with and without Fentanyl Citrate in Cow Calves. - Roonwal, G.; Shukla, B.P.; Shukla , S.; Jain, R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A study was planned to evaluate the efficacy of Levobupivacaine as an epidural analgesia, with and without Fentanyl Citrate and to evaluate the clinico-physiological changes. The study was conducted on 12 healthy cow calves, weighing between 50 to 70 kg. The animals were divided into two groups of six animals each. The animals of group 1 received Levobupivacaine (@ 0.8 mg/kg body wt.) in sacrococcygeal space, while animals of group 2 received Levobupivacaine (@ 0.8 mg/ kg. body wt.) and Fentanyl Citrate (@ 2 µg/kg body wt.) simultaneously in the sacrococcygeal space. The clinico-physiological changes were recorded at different time intervals in both treatments. The animals of treatment II showed longer duration and good depth as compared to animals of treatment I. The recovery was smooth in both groups. Rectal temperature, respiration rate and heart rate showed non-significant decrease in their values in both the groups.